Les stars et le cinéma d’animation - Bérénice Bonhomme (Mise au Point)
After Aladdin, the star (and the star persona) is an essential ingredient in making animated films. As it has become more common for the main characters in animated films to be voiced by prominent feature film stars, there has been much knowing playfulness, drawing on differences or similarities between the dubbing artist and his or her animated avatar. This article asks to what extent the image of the star comes into play in the creation of an animated character and in its reception by audiences – and whether the relationship is fruitful or not.